Ecotomografía transcraneana para el diagnóstico de enfermedad de Parkinson y otros trastornos del movimiento. Estudio piloto de 39 casos y su correlato clínico – radiológico - Venegas F., Pablo; Miranda G., Gonzalo; Sinning O., Mariana; Galleguillos G., Lorna (Revista Hospital Clínico Universidad de Chile, 2009)
Introduction: Parkinson disease diagnosis is based on physical neurologic exam, however sometimes ancillary tests could be needed. Transcranial sonography is a useful tool to perform Parkinson disease and others movement disorders diagnosis, showing pathologic hyperecogenicities of nigra substance and basal ganglia. Objective and methods: The objective of this study is to report the first 39 patients in whom transcranial sonography was performed. We recruit patients consulting to movement disorders unit at University of Chile hospital. Two independent investigators (PVF and GMG) blinded to clinical diagnosis performed transcranial sonography by temporal window. Considering clinical diagnosis as gold standard we calculated specificity and sensibility. Concordance between investigators was estimated too. Results: Concordance between investigators was 100%. Sensibility was 85.71% and specificity was 100%. Conclusion: According our report, transcranial sonography performed at University of Chile Hospital, is a high sensibility and specificity tool to support Parkinson disease and others movement disorders.